Black fungus gnats (Diptera: Sciaridae) of Queensland, Australia. Part II. Genus Pseudolycoriella Menzel & Mohrig, 1998 - Mohrig, Werner; Kauschke, Ellen; Broadley, Adam (Zootaxa, 2020)
In this second part on the black fungus gnats of Queensland, Australia, nine species are described as new for science. These are: Pseudolycoriella angustoantennata sp. n., Psl. breviradiata sp. n., Psl. consectaria sp. n., Psl. fuscovenosa sp. n., Psl. globostylata sp. n., Psl. notanda sp. n., Psl. paucispinata sp. n., Psl. secura sp. n. and Psl. unispinata sp. n. The following three species are new for Australia: Psl. bisulca Vilkamaa, Hippa & Mohrig, 2012, known from New Caledonia; Psl. snellingi Mohrig, 2013, reported from Papua New Guinea and Psl. horribilis (Edwards, 1931), described from Sumatra. All species are illustrated and keyed.